2022
DOI: 10.1097/jnr.0000000000000528
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of COVID-19-Related Stigma: A Qualitative Study on Nurses Caring for Patients With COVID-19

Abstract: BackgroundHealthcare workers caring for patients with Coronavirus Disease 2019 (COVID-19) have been a primary target of stigmatization and discrimination during the COVID-19 outbreak. Thus, there is an urgent need to develop a support system for Asian healthcare workers who care for patients with COVID-19.PurposeThis study was designed to understand the characteristics of COVID-19-related stigma experienced by nurses caring for patients with COVID-19.MethodsA qualitative content analysis methodology was used. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 38 publications
(43 reference statements)
2
9
0
Order By: Relevance
“…Therefore, older residents of Akita likely avoid chest X‐ray screening. Third, social stigma is reported to exist during the COVID‐19 pandemic, and people fear both COVID‐19 infection itself and social discrimination owing to infection 18–20 . Additionally, social discrimination tends to be stronger in areas with lower COVID‐19 prevalence, 19 suggesting that fear of social discrimination was strong in Akita Prefecture, where the COVID‐19 prevalence was lower 15 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, older residents of Akita likely avoid chest X‐ray screening. Third, social stigma is reported to exist during the COVID‐19 pandemic, and people fear both COVID‐19 infection itself and social discrimination owing to infection 18–20 . Additionally, social discrimination tends to be stronger in areas with lower COVID‐19 prevalence, 19 suggesting that fear of social discrimination was strong in Akita Prefecture, where the COVID‐19 prevalence was lower 15 .…”
Section: Discussionmentioning
confidence: 99%
“…Third, social stigma is reported to exist during the COVID-19 pandemic, and people fear both COVID-19 infection itself and social discrimination owing to infection. [18][19][20] Additionally, social discrimination tends to be stronger in areas with lower COVID-19 prevalence, 19 suggesting that fear of social discrimination was strong in Akita Prefecture, where the COVID-19 prevalence was lower. 15 Therefore, aging, distance and social stigma are among the reasons for the large decrease in the rate of chest X-ray screening in Akita.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, a study conducted by Mahamboro and colleagues (2020) in Indonesia who studied HIV-positive patients among married men stated that irrational fear of HIV transmission among healthcare workers leads to discrimination in healthcare settings, as it contributes to unwillingness to provide treatment to PLWHA. A similar result was obtained in Tsukuda et al (2022), which was designed to understand the characteristics of COVID-19-related stigma experienced by nurses caring for patients with COVID-19. The content analysis identified two categories and seven subcategories of stigma experienced by clinical nurses.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19-related stigma, experienced at high levels by healthcare workers, causes fear, anxiety, negative attitudes, ignoring behavior and rejection, and psychological discomfort, which can negatively affect their performance (39). In a tool designed by Tsukuda et al (2022), healthcare workers expressed their worries and anxiety about disclosing their workplace. They felt guilty and lthy because of their close contact with patients (40).…”
Section: Discussionmentioning
confidence: 99%
“…However, no COVID-19 social stigma scale has been designed for nurses of COVID ICUs, who are in direct contact with patients. The studies conducted in this context only reported some stigma characteristics, such as discrimination of family members (22), and did not comprehensively investigate social stigma characteristics in nurses.…”
Section: Introductionmentioning
confidence: 99%